2005
DOI: 10.1021/bi0480584
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Induced Hyperphosphorylation of Replication Protein A. 1. Identification of Novel Sites of Phosphorylation in Response to DNA Damage

Abstract: Replication protein A (RPA) is the predominant eukaryotic single-stranded DNA binding protein composed of 70, 34, and 14 kDa subunits. RPA plays central roles in the processes of DNA replication, repair, and recombination, and the p34 subunit of RPA is phosphorylated in a cellcycle-dependent fashion and is hyperphosphorylated in response to DNA damage. We have developed an in vitro procedure for the preparation of hyperphosphorylated RPA and characterized a series of novel sites of phosphorylation using a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 30 publications
2
65
0
Order By: Relevance
“…The middle subunit of RPA, RPA32, is phosphorylated primarily at two sites, serine 23 and serine 29, during the normal cell cycle in the G 1 /S transition, G 2 and M-phase, followed by dephosphorylation at the end of M-phase (Din et al, 1990). DNA-damaging agents known to stall replication, including UV, inhibitors of topoisomerase I and II and hydroxyurea (HU), induce hyperphosphorylation of RPA at additional serines and threonines on the N-terminus of RPA32, including serines 4, 8 and 33 and threonine 21 (Block et al, 2004;Nuss et al, 2005;Zernik-Kobak et al, 1997). RPA phosphorylation is thought to modulate protein-protein interactions as well as its ability to bind dsDNA (Abramova et al, 1997;Binz et al, 2003;Liu et al, 2005;Patrick et al, 2005;Yoo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The middle subunit of RPA, RPA32, is phosphorylated primarily at two sites, serine 23 and serine 29, during the normal cell cycle in the G 1 /S transition, G 2 and M-phase, followed by dephosphorylation at the end of M-phase (Din et al, 1990). DNA-damaging agents known to stall replication, including UV, inhibitors of topoisomerase I and II and hydroxyurea (HU), induce hyperphosphorylation of RPA at additional serines and threonines on the N-terminus of RPA32, including serines 4, 8 and 33 and threonine 21 (Block et al, 2004;Nuss et al, 2005;Zernik-Kobak et al, 1997). RPA phosphorylation is thought to modulate protein-protein interactions as well as its ability to bind dsDNA (Abramova et al, 1997;Binz et al, 2003;Liu et al, 2005;Patrick et al, 2005;Yoo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of the 32-kDa subunit of RPA2 is well characterized in these processes. At least 10 phosphorylation sites (Ser-4, Ser-8, Ser-10, Ser-11, Ser-12, Thr-21, Ser-23, Ser-29, Ser-33, and Thr-98) and 4 kinases (ATM, ATR, DNA-PKcs, Cdk1, and Cdk2) have been suggested (25)(26)(27)(28)(29)(30)(31)(32). It is shown that DNA damage-induced RPA hyperphosphorylation is critical for Rad51 recruitment and HR-mediated repair after replication block but is not essential for IR and I-Sce-I endonuclease-stimulated HR (28).…”
mentioning
confidence: 99%
“…Of the ϳ70-kDa (RPA1), 30-kDa (RPA2), and 14-kDa (RPA3) subunits, human RPA is subject to extensive phosphorylation on RPA2 (2) and at one RPA1 site (15). The N-terminal 33 residues of RPA2 undergo both cell cycle-and stress-dependent phosphorylation on approximately nine sites (Fig.…”
mentioning
confidence: 99%